2004
DOI: 10.1016/j.bbadis.2003.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The urea cycle and related pathways in the liver of Walker-256 tumor-bearing rats

Abstract: The urea cycle was evaluated in perfused livers isolated from cachectic tumor-bearing rats (Walker-256 tumor). Urea production in livers of tumor-bearing rats was decreased in the presence of the following substrates: alanine, alanine + ornithine, alanine + aspartate, ammonia, ammonia + lactate, ammonia + pyruvate and glutamine. Urea production from arginine was higher in livers of tumor-bearing rats. No difference was found with aspartate, aspartate + ammonia, citrulline, citrulline + aspartate and glutamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 16 publications
6
35
0
Order By: Relevance
“…This is an unexpected finding because it has been observed that in both arthritic and tumour-bearing rats, ureagenesis from alanine and other substrates is considerably diminished and that this diminution correlates with the diminution of gluconeogenesis (Yassuda-Filho et al 2003;Corbello-Pereira et al 2004). However, it must stressed that a diminution of glucose production from alanine without a corresponding change in urea plus ammonia production represents an apparent unbalance between the carbon and nitrogen fluxes.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This is an unexpected finding because it has been observed that in both arthritic and tumour-bearing rats, ureagenesis from alanine and other substrates is considerably diminished and that this diminution correlates with the diminution of gluconeogenesis (Yassuda-Filho et al 2003;Corbello-Pereira et al 2004). However, it must stressed that a diminution of glucose production from alanine without a corresponding change in urea plus ammonia production represents an apparent unbalance between the carbon and nitrogen fluxes.…”
Section: Discussionmentioning
confidence: 93%
“…This alteration is diminution of gluconeogenesis from alanine, which has been reported to occur in rats with sepsis (Filkins & Cornell 1974;Spitzer et al 1985), adjuvant-induced arthritis (Fedatto-Jr et al 1999;Yassuda-Filho et al 2003) and rats bearing malignant tumours such as the Walker-256 tumour (Williams & Siddiqui 1990;Corbello-Pereira et al 2004) and mammary adenocarcinoma (Liu et al 1990). Each factor alone, TNFa and IL1b, was able to induce inhibition of gluconeogenesis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…3 Gluconeogenesis and ureogenesis from alanine, on the other hand, are also lower in livers from tumour-bearing rats. 4,5 Furthermore, the presence of the Walker-256 tumour does not affect hepatic gluconeogenesis from substrates such as lactate and pyruvate when the latter are infused in the presence of high and non-physiological ammonia concentrations (0.5 mM). 5 These results are in clear contrast with results obtained with animals bearing several other types of tumours in which stimulation of hepatic gluconeogenesis was found.…”
Section: Introductionmentioning
confidence: 99%